1967
DOI: 10.21236/ad0666914
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Buckling and Snapping Under Dynamic Load

Abstract: Publication of this report does noL constitute Air Force approval of the report's findings or conclusions, It is published only for the exchange and stimulation of ideas.Dennis R. Cochran, Lt., USAF Project OfficerThe behavior of a shallow arch and a thin ring ,der a dynamic pulse loading is studied for a wide range of g.ometric and load parameters. The nonlinear dynamic response and static load deflection characteristics of the systems are related and employed to define dynamic elastic snapping and dynamic el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Therefore, an average diameter 185 (defined as the mean of the smallest and largest number given in Table B2) was calculated. The curve radii and 186 bifurcation angles have been estimated based on illustrations and data in [8][9][10][11][12][13][14][15][16][17][18][19] , and are given in Tables B3 and B4, 187 respectively. 188…”
Section: Author Contributionsmentioning
confidence: 99%
“…Therefore, an average diameter 185 (defined as the mean of the smallest and largest number given in Table B2) was calculated. The curve radii and 186 bifurcation angles have been estimated based on illustrations and data in [8][9][10][11][12][13][14][15][16][17][18][19] , and are given in Tables B3 and B4, 187 respectively. 188…”
Section: Author Contributionsmentioning
confidence: 99%
“…Lock [13] found that if the load duration (dt) is sufficiently small (i.e., the step load becomes an impulsive load), a column can sustain higher loads than under static loading. In other words, in dynamic loading conditions, the impulse imparted to the structure rather than the size of the load becomes the most significant load parameter (see Budiansky in [14] for an analytical description).…”
Section: Dynamic Loadingmentioning
confidence: 99%
“…Lock et al [180] showed that dynamic loads, such as step loads and impulses, much in the excess of static buckling loads can be applied on the penetration tool, as long as they are removed fast enough. Therefore, the high-speed impact force tools, such as used in the axially vibrating Vibrational Angioplasty Device (Medical Miracles, UK), Crosser catheter (FlowCardia, Sunnyvale, CA; designed for peripheral chronic occlusions), and the device proposed by Rubenchik et al [61], may have an increased buckling resistance over the static tools.…”
Section: ) Increase the Applied Forcementioning
confidence: 99%